Math, asked by ssanjmukhi, 11 days ago

Expand: ( 3 + √2)^2

Hi, can anyone please help me with this

Answers

Answered by poonamlovy82
1

Step-by-step explanation:

(3+√2)^2

=(3)^2+(√2)^2+2×3×√2

= 9+2+6√2

=11+6√2

Answer will be 11+62

Mark me as brainliest.

Answered by sureshraiiskcon
0

Answer:

( 3+ 2 ) 4⇒ 4 C 0

( 3 ) 4 + 4 C 1

( 3) 3 ( 2 )+ 4 C 2

(

3

)

2

(

2

)

2

+

4

C

3

(

3

)(

2

)

3

+

4

C

4

(

2

)

4

⇒1(3)

2

+4.(3

3

)(

2

)+

2

4×3

(3)(−2)+4(

(

3)(2

2

)+1(2)

2

⇒9+12

6

+36+8

6

+4

⇒(49+20

6

)

Similar questions